Psychosocial Impact and Protective Factor of COVID-19 Confirmed Patient During Isolation Enactment: A Systematic Review - Mira Wahyu Kusumawati; Setyawati Soeharto; Heni Dwi Windarwati (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: An individual who is positively confirmed COVID-19 is required to undergo a longterm isolation. As a consequence, this condition can cause physical and psychosocial impacts. This review article aims to identify psychosocial impacts COVID-19 patients and protective factors the patients during isolation enactment. Method: This article is a systematic review by doing article identification from four data bases (ScienceDirect, ProQuest, EBSCO and PubMed) published between January to October 2020. The articles were selected using PRISMA based on assigned inclusion and exclusion, keywords on psychological impact, COVID-19, and confirmed patient. Results: Based on the 28 article analysis divides psychosocial domain into four aspects; they are emotional impact, social, and behavior. Protective factor was divided into four aspects, they are social support (family, social, medical team, and government support), personal ability (religious, cognitive, affective, psychomotor aspects), positive belief (internal and external), and material asset (facility and financial). Conclusion: Psychosocial impacts of confirmed COVID-19 patients during isolation enactment can be minimized through psychologist intervention by increasing patients’ protective factors. Based on the finding, the suggestion was the part of nursing in isolation COVID-19 important to increase health condition of mental patients undergo isolation.